MIL ROSAS ROUBADAS, BY SILVIANO SANTIAGO: FROM MOURNING TO THE BIRTH OF THE FICTION WRITER - Cardoso de Freitas Lima, Leila Aparecida [UNESP]; Busato, Susanna [UNESP] (Univ Estadual Mato Grosso Sul, 2021)
The theme of this work is the relationship between the narrator and his memories in the novel Mil rosas roubadas, by Silviano Santiago. The objective is to investigate the role of Zeca's death in the narrator-writer's self-discovery process. Therefore, it is based on the hypothesis that the friend's death forces the narrator-character to dive into a writing process that will be able to unravel feelings not understood in the past, in addition to causing a redefinition of the condition of her self in the world. In this path, the starting point for the analysis is based on the narratological studies of Gerard Genette (1979), however, during this process authors such as Freud (1930) and (2011), Bakhtin (1997), Gagnebin (2006), among others will also be invited to the discussion. This reflection intends to result in the understanding of a supposed paradoxical presence of death and life in Santiago's novel. In this context, it is possible that the death of the narrated self needs to be decreed together with Zeca's, so that the self of the enunciation with its new fictionalist face can finally be born.
Keywords: Narrator; Mourning; Birth; Mil rosas roubadas; Silviano Santiago